2018
DOI: 10.1016/s0140-6736(18)31543-5
|View full text |Cite|
|
Sign up to set email alerts
|

Awareness of fetal movements and care package to reduce fetal mortality (AFFIRM): a stepped wedge, cluster-randomised trial

Abstract: SummaryBackground2·6 million pregnancies were estimated to have ended in stillbirth in 2015. The aim of the AFFIRM study was to test the hypothesis that introduction of a reduced fetal movement (RFM), care package for pregnant women and clinicians that increased women's awareness of the need for prompt reporting of RFM and that standardised management, including timely delivery, would alter the incidence of stillbirth.MethodsThis stepped wedge, cluster-randomised trial was done in the UK and Ireland. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
162
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(172 citation statements)
references
References 21 publications
9
162
1
Order By: Relevance
“…The high rates of intervention, in the form of induction of labor and cesarean section, and of use of resources, in the form of admission and ultrasound, are clear. The AFFIRM study showed similar prelabor cesarean section rates and induction rates that were nearly as high . Less than 40% of women with recurrent RFM in our cohort have a spontaneous onset of labor, reflecting current advice in the UK in the Royal College of Obstetricians and Gynaecologists, Greentop Guideline 2011…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The high rates of intervention, in the form of induction of labor and cesarean section, and of use of resources, in the form of admission and ultrasound, are clear. The AFFIRM study showed similar prelabor cesarean section rates and induction rates that were nearly as high . Less than 40% of women with recurrent RFM in our cohort have a spontaneous onset of labor, reflecting current advice in the UK in the Royal College of Obstetricians and Gynaecologists, Greentop Guideline 2011…”
Section: Discussionsupporting
confidence: 67%
“…It is accepted that SGA babies are over‐represented among pregnancies with RFM. The latter can be a presentation of fetal demise, for which SGA is a major risk factor . Without a control group, we cannot confirm this in our cohort of pregnancies.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations